Spatial monopoly pricing under non-constant marginal costs - Marten Graubner (Letters in Spatial and Resource Sciences, 2020)
The firm's price policy decision is a central issue in spatial economics. Previous results show, e.g., that the specification of consumers' demand functions is pivotal but mostly mill and uniform pricing are compared in a monopoly setting with constant marginal costs. The results in this paper highlight that some conclusions of prior work do not hold if the monopolist operates under non-constant marginal production costs. For instance, the optimal price is no longer independent of transport costs, and the welfare ranking of mill and uniform pricing also depends on the shape of the cost function.
Keywords: D42; L11; R32; 330; spatial pricing; price discrimination; monopoly